Implementasi Undang-Undang Nomor 8 Tahun 2015 tentang Pemilihan Gubernur, Bupati dan Walikota pada Pilkada Serentak Tahun 2015 (Studi Kasus pada Pelaksanaan Pilkada di Kabupaten Malang, Provinsi Jawa Timur Tahun 2015) - Nurakhmadi, Dito Arief (Jurnal Ilmiah Administrasi Publik, 2020)
With the presence of Law No. 8 of 2015 concerning Amendments to Law No. 1 of 2015 concerning Stipulation of Government Regulation in Lieu of Law No. 1 of 2014 concerning Regional Head Elections, there are a number of changes to the rules related to the mechanism for the implementation of Regional Head Elections directly and simultaneously. This study aims to describe the implementation of Law No. 8 of 2015 concerning the Election of Governors/ Regents/ Mayors in Organizing Pilkada in Malang Regency 2015. The research method used is descriptive qualitative method. The findings suggesst the product evaluation in the case of the evaluation of the Malang District Election policy in 2015 is the final result of the policy evaluation which can be used as an improvement in the new Election Law, both legally and in its implementation. UU no. 8 of 2015 concerning the Election of Governors, Regents and Mayors in the Simultaneous Local Election in 2015 has many shortcomings that can be said to be bad policy, and has several shortcomings in terms of implementation.